Be a Mom: Formative Evaluation of a Web-Based Psychological Intervention to Prevent Postpartum Depression. Issue 4 (November 2018) - Fonseca, Ana; Pereira, Marco; Araújo-Pedrosa, Anabela; Gorayeb, Ricardo; Ramos, Mariana Moura; Canavarro, Maria Cristina
Abstract: A formative evaluation (consisting of two phases: a scoping literature review and a focus group with mental health professionals) was conducted to inform the design of a web-based intervention to prevent postpartum depression, in terms of its characteristics and content: the Be a Mom program. The results showed that the web-based intervention should be short-term, delivered postnatally, and grounded in cognitive-behavior therapy principles. Moreover, the intervention should include weekly sessions targeting basic contents: motherhood changes, reorganizations and emotional experience; cognitions, self-criticism, and self-compassion; parenting values, social support, and assertive communication skills; couple relationship, negotiation and conflict resolution skills; and postpartum depression signs and professional help-seeking. These results may improve the Be a Mom's adequacy, implementation success, and effectiveness. Highlights: The CBT web-based intervention is short-term, and delivered postpartum The intervention has 5 modules updated weekly, each addressing a thematic content Acceptance and compassion-focused principles should be considered Interactive and human features are included in the intervention Formative evaluation may improve the intervention implementation and effectiveness